Child nutritional status in poor Ethiopian households - Mekonnen, A; Tefera, B; Woldehanna, T; Jones, N; Seager, J; Alemu, T; Asgedom, G (Young Lives (Project), DFID (University of Oxford), 2005)
Ethiopia is one the world’s poorest countries with one of the highest rates of child malnutrition. The poor nutritional status of Ethiopian children is well documented, but the causes and relative importance of various determinants of malnutrition are not well understood. Ethiopia thus lacks an integrated cross-sectoral policy to guide nutrition programmes and interventions. While the literature on child malnutrition suggests gender- and location-related differences in malnutrition rates, this has not been investigated in detail, particularly in Ethiopia. Other factors such as household composition (sex and age), social capital, marital status, economic shocks and food aid are presented in the literature, but their impacts are little discussed. This paper shows that priority should not be given to one element of infant malnutrition – such as food security, public health or gender. Ensuring better nutrition for children requires a strategic, evidence-informed combination of approaches. Based on Young Lives research in Ethiopia, it explores some of the less obvious factors affecting children’s nutritional status. The overall objective is to examine the causes of children’s nutritional status using weight-for-height z-score (WHZ), an internationally accepted indicator. The paper focuses on considering differences between boys and girls and urban and rural areas. Since many of these children are engaged in paid or unpaid work, an attempt is also made to find out whether there is any relationship between child wasting (acute malnutrition with low weight-for-height) and child work.